Quarter Life Crisis di Masa Dewasa Awal: Studi Pada Pemuda Jawa yang Belum Bekerja - Joti Dyana Handayani; Doddy Hendro Wibowo (Pusat Riset dan Inovasi Nasional, 2026)
Quarter life crisis is a phase of identit, emotional, and life purpose crisis commonly experienced during early adulthood, especially when faced with pressure related to life achievements, employment, and social expectations. this study aims to describe the dynamics of quarter lufe crisis experienced by unemployed Javanese young adults. a qualitative approach using a case study method was employed to understand the participants subjective experiences. Data were collected through in depth interview with three informants aged 18-29 ears, residing in Central Java, who were currently unemployed. The findings show that these young Javanese individuals tend to experience symptoms of quarter life crisis such as anxiety about the future, feelings of worthlessness, social pressure from family and surroundings, and confusion about life direction. Moreover, the patriarchal nature of Javanese culture adds further pressure on the informants. This study concludes that the quarter life crisis among Javanese young adults has unique characteristics shaped by cultural context and socioeconomic conditions. These findings are expected to serve as a foundation for developing more culturally contextual psychological interventions and contribute to cross cultural studies on early adulthood development.